PELATIHAN AKUNTANSI BAGI PENGELOLA KOPERASI DI DINAS PERDAGANGAN DAN KOPERASI (DINDAGKOP) UKM KABUPATEN DEMAK - Mohklas Mohklas; Nurrohmi Ambar Tasriastuti; Endang Kurniawati (Buletin Abdi Masyarakat, 2023)
The purpose of the financial statements is to provide an overview of the financial position and measure the financial performance of an entity in the period concerned. The main task of a financial manager is to help companies organize, manage, plan, evaluate matters related to company finances. The tools for analyzing financial reports are liquidity ratios, solvency ratios, and profitability ratios. Financial analysis and reports will later be used as a basis for making the right financial decisions. The problem with Cooperatives in Demak Regency is that there are still managers or administrators who are unable or lack mastery in compiling and analyzing their financial reports. The limited competence of human resources is one of the reasons for the low quality of the financial reports presented. This will have an impact on the postponement of the implementation of the Annual Member Meeting as well as decision making related to the performance of cooperative financial reports. The obligation of administrators to organize Annual Member Meeting becomes commonplace every year, in order to submit management and supervisor accountability reports to members for the management and supervision of cooperatives. Cooperatives require more understanding and training regarding the preparation of financial reports and performance analysis. The priority solutions are first, facilitating cooperatives in preparing cooperative financial reports, second, technical training in analyzing the performance of financial reports that are more adequate, and third, how to implement a cooperative's internal control system. Keywords: Financial Report Performance, Liquidity Ratios, Solvency and Profitability